Charmonium in nuclear matter and nuclei - Martínez, J.J. Cobos; Tsushima, K.; Krein, G. [UNESP]; Thomas, A. W. (My University, 2021)
We present results for the ηc-nucleus bound state energies for various nuclei using an effective Lagrangians approach. The attractive potentials for the ηc in the nuclear medium originate from the medium-modified intermediate DD∗ state in the ηc self energy, using the local density approximation. Our results suggest that the ηc should form bound states with all the nuclei considered.